SQL Server 2008 Transact-SQL Recipes A Problem-Solution Approach - Sack, Joseph; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2008)
SQL Server 2008 Transact–SQL Recipes: A Problem–Solution Approach is an example–based guide to the Transact–SQL language that is at the core of SQL Server 2008. Learn to create databases, insert and update data, generate reports, secure your data, and more. Author Joseph Sack takes common Transact–SQL tasks and breaks them down into a problem/solution format that is quick and easy to read so that you can get the job done fast when the pressure is on. Focused on solutions: Look up what you need to do. Learn how to do it. Do it. Current: Newly updated for SQL Server 2008 Comprehensive: Covers 30 different Transact–SQL problem domains.
Select -- Perform, Capture, and Track Data Modifications -- Transactions, Locking, Blocking, and Deadlocking -- Tables -- Indexes -- Full-Text Search -- Views -- SQL Server Functions -- Conditional Processing, Control-of-Flow, and Cursors -- Stored Procedures -- User-Defined Functions and Types -- Triggers -- CLR Integration -- XML, Hierarchies, and Spatial Data -- Hints -- Error Handling -- Principals -- Securables, Permissions, and Auditing -- Encryption -- Service Broker -- Configuring and Viewing SQL Server Options -- Creating and Configuring Databases -- Database Integrity and Optimization -- Maintaining Database Objects and Object Dependencies -- Database Mirroring -- Database Snapshots -- Linked Servers and Distributed Queries -- Query Performance Tuning -- Backup and Recovery.
Keywords: Database management; Software engineering; Database Management; Software Engineering/Programming and Operating Systems